Oxidative Stress in Calcific Aortic Valve Stenosis: Protective Role of Natural Antioxidants - Radhika Adhikari; Saugat Shiwakoti; Ju-Young Ko; Bikalpa Dhakal; Sin-Hee Park; Ik Jun Choi; Hyun Jung Kim; Min-Ho Oak (Antioxidants, 2022)
Calcific aortic valve stenosis (CAVS) is the most prevalent heart valvular disease worldwide and a slowly progressive disorder characterized by thickening of the aortic valve, calcification, and subsequent heart failure. Valvular calcification is an active cell regulation process in which valvular interstitial cells involve phenotypic conversion into osteoblasts/chondrocytes-like cells. The underlying pathophysiology is complicated, and there have been no pharmacological treatments for CAVS to date. Recent studies have suggested that an increase in oxidative stress is the major trigger of CAVS, and natural antioxidants could ameliorate the detrimental effects of reactive oxygen species in the pathogenesis of CAVS. It is imperative to review the current findings regarding the role of natural antioxidants in CAVS, as they can be a promising therapeutic approach for managing CAVS, a disorder currently without effective treatment. This review summarizes the current findings on molecular mechanisms associated with oxidative stress in the development of valvular calcification and discusses the protective roles of natural antioxidants in the prevention and treatment of CAVS.